Pewarna Karmin untuk Produk Makanan dan Kosmetik: Studi Perbandingan Fatwa Indonesia dan Yordania - Yusrizal, Navis; Hanna, Siti; Haikal, Muhammad Danial (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The utilization of the istinbath method in determining the legal framework concerning the use of carmine dye in various fatwa institutions, including the Indonesian Ulema Council and Da'irah al-Ifta' Jordan, remains a subject of ongoing discourse and deliberation. This study compares the istinbath method for determining the carmine law between the Indonesian Ulema Council and Dairah al-Ifta’ Jordan and the istihalah process in manufacturing carmine dye. The research method uses normative juridical with a conceptual approach and comparative law. The findings of this study indicate that the Indonesian Ulema Council and Da’irah al-Ifta’ both permit carmine dye, but with different istinbath methods. The Indonesian Ulema Council likens Carmine to grasshoppers because they have many similarities. On the other hand, Dairah al-Ifta’ considers that carmine dye has undergone the istihalah process. The similarities between the Fatwa of the Indonesian Ulema Council and the Fatwa of Da’irah al-Ifta’ Jordan include: 1) both state that carmine is an insect and, 2) both institutions also state that the use of carmine dye must be based on the condition that it is not harmful to humans. The process of making carmine dye undergoes the istihalah process according to the Hanafi and Maliki schools, involving changing one substance to another and changing from something bad to something good. This research contributes to the development of science related to the determination of the Fatwa on the use of carmine dye and references for the Muslim community in related matters.